Mahasiswa Kuliah Kerja Nyata Kelompok 75 dan Masyarakat dalam Kegiatan Pemanfaatan Daun Kering untuk Meningkatkan Kreativitas Anak Melalui Karya Seni Kolase - Pratiwi, Enjel; Sumarni, Yenti; Herlyna, Echa Shefty; Febiola, Dina; Utami, Meizelin AdeUtami; Renanda, Angelia Retno; Silviyana, Silviyana; Maharani, Resti; Rifa’i, Ahmad; Arianda, Ceksa; Juliustio, Agung (PPSDP Undergraduate Journal of Educational Sciences, 2024)
Real work lectures (KKN) are one of the community services programs that students must take part in as part of the Tri Dharma of Higher Education. This research is one of the implementations of KKN activities that focuses on education. The activity of making collages using dry leaves in Niur Dusun III Village provides a fun creative experience for children, improving their fine motor skills and creativity. This article discusses the use of dry leaves in collage art to develop children’s potential. Art education was considered important, and collage was an effective method for practicing these skills. This activity involves an introduction to collage, guided practice, and evaluation to measure its effectiveness. The results show the children’s enthusiasm and their ability to learn various skills through collage, which supports their motor and intelligence development.